Seismic performance of buildings with novel self‐centering base isolation system for earthquake resilience - Wang, Bin; Chen, Peng; Zhu, Songye; Dai, Kaoshan (Earthquake engineering & structural dynamics, 2023)
This study presents a novel self‐centering (SC) base isolation system enabled by traditional lead rubber bearing (LRB) incorporating superelastic shape memory alloy (SMA) U‐shaped dampers (hereinafter referred to as SMA‐LRB). This system is particularly suitable for some important structures (e.g., hospital buildings) that require high seismic performance and rapid recovery of normal serviceability after a severe earthquake. The working mechanism of the SMA‐LRBs is first illustrated, followed by a comparative experimental study on the traditional LRB and the emerging SMA‐LRB. Test results confirm the satisfactory flag‐shaped hysteresis loops of SMA‐LRB associated with significantly reduced residual deformation under cyclic loading. Subsequently, a refined numerical modeling strategy for these bearings is developed. The seismic performances of the SMA‐LRBs are examined systematically through two comparative reinforced concrete (RC) frame buildings, namely, the traditionally isolated and the SC isolated cases under far‐ and near‐field earthquakes. Seismic fragility analyses are further carried out through incremental dynamic analysis (IDA). The seismic responses demonstrate that the SC isolated building can match or improve the behavior of the traditional isolated buildings. Compared with the considerable residual deformation of the traditional isolated system under some earthquake events, the SC isolated system exhibits negligible residual deformation that can significantly avoid normal serviceability disruption while achieving the high‐performance objectives. The SC base isolation system can provide a promising type of advanced seismic protection device for earthquake resilient design.